Zeolite Nanoparticles Loaded with 2-Methoxystradiol as a Novel Drug Delivery System for the Prostate Cancer Therapy - Cardenas-Sankan, G; Orihuela-Diaz, P; Casagrande-Denardin, J; Elgueta-Bravo, E (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
The estrogen metabolite 2-methoxyestradiol (2ME) is a promissory anticancer drug mainly because of its pro-apoptotic properties in cancer cells. However, the therapeutic use of 2ME has been hampered due to its low solubility and bioavailability. Thus, it is necessary to find new ways of administration for 2ME. Zeolites are inorganic aluminosilicates with a porous structure and are considered good adsorbents and sieves in the pharmaceutical field. Here, mordenite-type zeolite nanoparticles were loaded with 2ME to assess its efficiency as a delivery system for prostate cancer treatment. The 2ME-loaded zeolite nanoparticles showed an irregular morphology with a mean hydrodynamic diameter of 250.9 ± 11.4 nm, polydispersity index of 0.36 ± 0.04, and a net negative surface charge of −34 ± 1.73 meV. Spectroscopy with UV-vis and Attenuated Total Reflectance Infrared Fourier-Transform was used to elucidate the interaction between the 2ME molecules and the zeolite framework showing the formation of a 2ME-zeolite conjugate in the nanocomposite. The studies of adsorption and liberation determined that zeolite nanoparticles incorporated 40% of 2ME while the liberation of 2ME reached 90% at pH 7.4 after 7 days. The 2ME-loaded zeolite nanoparticles also decreased the viability and increased the mRNA of the 2ME-target gene F-spondin, encoded by SPON1, in the human prostate cancer cell line LNCaP. Finally, the 2ME-loaded nanoparticles also decreased the viability of primary cultures from mouse prostate cancer. These results show the development of 2ME-loaded zeolite nanoparticles with physicochemical and biological properties compatible with anticancer activity on the human prostate and highlight that zeolite nanoparticles can be a good carrier system for 2ME. © 2023 by the authors.